2023
DOI: 10.3390/coatings13030621
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Dependence of Electrocatalytic Activity of Copper and Palladium Nanoparticles on Morphology and Shape Formation

Abstract: A synthesis strategy for the manufacture of inexpensive highly efficient nanostructured catalysts has been developed. The developed unique nonplatinoid copper-based catalysts with different surface morphology were investigated as a functional layer with high activity in the ethanol oxidation in alkaline media. A modifying layer with controlled morphology, composition, and excellent electrocatalytic activity was synthesized by electrochemical deposition by varying such synthesis parameters as deposition tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…“Hydrogen carriers” are hydrogen-chemisorbing substances such as platinum metals [ 54 ]. The nanostructured palladium layer formation on the membrane surface will increase the actual working surface area, thus leading to an increase in the number of chemisorption centers [ 55 , 56 ]. The deposition of a modifier based on pentagonal structured, multiply twinned nanoparticles is particularly interesting and effective.…”
Section: Introductionmentioning
confidence: 99%
“…“Hydrogen carriers” are hydrogen-chemisorbing substances such as platinum metals [ 54 ]. The nanostructured palladium layer formation on the membrane surface will increase the actual working surface area, thus leading to an increase in the number of chemisorption centers [ 55 , 56 ]. The deposition of a modifier based on pentagonal structured, multiply twinned nanoparticles is particularly interesting and effective.…”
Section: Introductionmentioning
confidence: 99%
“…Doping foreign high-active transition metal into nickel sulfide-based catalysts is regarded as an efficient route to optimize their electrochemical performance by overcoming the intrinsic activation barriers [39][40][41]; however, the doping strategy usually shows a tendency to include the various metal-active sites, leading to a significant impact on the study of intrinsic catalytic activity [42,43]. In principle, the catalytic property of a material is determined using its electronic structure and can be regulated by engineering its composition and morphology [44][45][46]. The internal and external adjustments, i.e., tuning the electronic structure through phase control and composition adjustment, are valid for the production of efficient electrocatalysts [47][48][49].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that hydrogen permeability of membranes increased after each stage, as the use of the air heat treatment technique directly affected the increase in the effective surface area of the membrane. Another way to activate the membrane surface is its modification with powdered catalytically active particles [33][34][35][36]. The most promising way is the application of nanoparticles, which have become widespread in many areas of science and industry due to the unusual physical and chemical properties of nanoparticles [37][38][39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%